2006
DOI: 10.1111/j.1540-8191.2006.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Revascularization in Patients with Low Ejection Fraction <=35%: Effect of Pump Technique on Early Morbidity and Mortality

Abstract: Background and aim: Left ventricular dysfunction is an important predictor of in-hospital mortality. Surgical risk among these patients remains high. The present study is conducted to evaluate the difference in early morbidity and mortality among patients with compromised left ventricular function (LVF) after myocardial revascularization using either off-pump or on-pump coronary artery bypass graft. Methods: Between April 2000 and April 2004, 150 patients with ejection fraction (EF) ≤35% underwent isolated cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 25 publications
(35 reference statements)
11
35
2
1
Order By: Relevance
“…We believed that the surgeons have different indications about IABP insertion and it seems that the use of IABP is dependent on the surgeons' perception. Also, because of the shorter perfusion time and cross-clamp time in our research in comparison with other previous reports in Iran [30] and other countries, [31][32][33] our data about the frequency of IABP insertion could be lower than the other reports.…”
Section: Discussioncontrasting
confidence: 54%
“…We believed that the surgeons have different indications about IABP insertion and it seems that the use of IABP is dependent on the surgeons' perception. Also, because of the shorter perfusion time and cross-clamp time in our research in comparison with other previous reports in Iran [30] and other countries, [31][32][33] our data about the frequency of IABP insertion could be lower than the other reports.…”
Section: Discussioncontrasting
confidence: 54%
“…6,7) Recent studies have reported early postoperative mortality rates of 1.7%-11% in patients with LVD. 1,[6][7][8][9][10][11][12][13][14][15][16][17] The operative mortality rate in this study (2.5%) was similar to that reported in other studies, indicating the safety of the off-pump technique for patients with LVD.…”
Section: Discussionsupporting
confidence: 85%
“…In off-pump patients, Darwazah et al reported in 150 patients a rate of 6.1% [14], Ascione et al in 74 patients 7% [6], Tugtekin et al with 6.5% [15], smaller rates were observed by Arom et al with 4.4% [16]. The reason for the low mortality rate in the present study can be explained by the strict in-and exclusion criteria, thereby affecting the long-and short-term outcome [17].…”
Section: End-diastolic Volume MLcontrasting
confidence: 65%